Wprowadzenie dzieci w tajemnicę Ducha Świętego w środowisku rodzinnym - Osewska, Elżbieta (Studia Pastoralne, 2008)
Most specialists in pedagogy and catechetics agree that in the process of introducing children to the mystery of the Holy Spirit, parents should not concentrate as much on a speculative way of presenting Holy Spirit, but rather unite and combine children’s everyday experiences with faith reality. The first task of Christian parents should not be the transmission of Catechism, but the care of creating childhood full of love, trust, respect, forgiveness and joy. Only on the basis of faith experiences parents may start to talk with children about the Holy Spirit using correct, interesting and rather simple words. Of significant role in this process is the person of Jesus Christ. Listening to his words the child will discover the Holy Spirit not as an „anonymous Power,” but as a person, who is present in the Church, keeping vigil over Church development and inspiring Christians for opening, creativity, conversions and perfecting life.